2019
DOI: 10.1128/aac.00583-19
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Understanding Antimicrobial Drug Dosing in Critically Ill Patients on Renal Replacement Therapy

Abstract: A careful management of antimicrobials is essential in the critically ill with acute kidney injury, especially if renal replacement therapy is required. Acute kidney injury may lead per se to clinically significant modifications of drugs' pharmacokinetic parameters, and the need for renal replacement therapy represents a further variable that should be considered to avoid inappropriate antimicrobial therapy. The most important pharmacokinetic parameters, useful to determine the significance of extracorporeal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 105 publications
(159 reference statements)
0
86
0
3
Order By: Relevance
“…The SC and the SA indicate the ratio of solute concentration in ultrafiltrate (SC) or the dialysate (SA) to solute concentration in the blood (Wong et al, 2015). CRRT clearance can be calculated by SC/SA and effluent flow rates as follows: convention clearance (ml/min) = SC × ultrafiltrate flow rate (ml/min); diffusion clearance = SA × dialysate flow rate (ml/min) (Pistolesi et al, 2019). SC or SA = 0 represents all drugs cannot pass through the membranes, while SC or SA =1 represents that all drugs can be filtered through the CRRT membrane.…”
Section: Crrt Membranementioning
confidence: 99%
See 2 more Smart Citations
“…The SC and the SA indicate the ratio of solute concentration in ultrafiltrate (SC) or the dialysate (SA) to solute concentration in the blood (Wong et al, 2015). CRRT clearance can be calculated by SC/SA and effluent flow rates as follows: convention clearance (ml/min) = SC × ultrafiltrate flow rate (ml/min); diffusion clearance = SA × dialysate flow rate (ml/min) (Pistolesi et al, 2019). SC or SA = 0 represents all drugs cannot pass through the membranes, while SC or SA =1 represents that all drugs can be filtered through the CRRT membrane.…”
Section: Crrt Membranementioning
confidence: 99%
“…A standard dose of these antimicrobials can be recommended for patients during CRRT. Although little is known about the PK parameters of clindamycin and azithromycin during different CRRT modalities, considering their non-renal elimination, studies suggested that no dose adjustment is required during CRRT (Pistolesi et al, 2019).…”
Section: Antimicrobials Which Do Not Need Dosing Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Such heterogeneity is further compounded by physiological derangements associated with critical illnesses, renal replacement therapy, drug-drug interactions, genetic polymorphisms and the use of ECMO. [49][50][51][52] Much deeper understanding of the interplay between these factors is critical in improving our ability to provide personalized dosing to pediatric patients on ECMO. Pediatric pharmacokinetic research presents specific challenges, some of which can be circumvented with the use of model-based approaches to study design and analysis, such as population pharmacokinetic modeling and physiologically based pharmacokinetic modeling.…”
Section: Discussionmentioning
confidence: 99%
“…74 Pharmacokinetics of drugs could be altered during RRT. 75 For patients receiving hemodialysis or peritoneal dialysis, the dosage of chloroquine should be as same as patients with GFR< 10 mL/min, namely, administer 50% of the original dose. For patients receiving CRRT, no dosage adjustment is necessary.…”
Section: Antiviral Agents In Covid-19 Patients Receiving Renal Replacmentioning
confidence: 99%